New insights into the taxonomy of Trechus Clairville, 1806 (Coleoptera: Carabidae) in the Balkans, with the first description of the male of Trechus bohemorum Pawlowski, 1973 - Kostova, Rumyana; Bekchiev, Rostislav (Zootaxa, 2025)
Following examination of the type series of Trechus bohemorum Pawlowski, 1973 in the National Museum in Prague (Czech Republic), a male specimen of this species was identified in the collection of the Faculty of Biology, Sofia University. This represents the first record of a male for this species in Bulgaria previously known only from two female specimens. A complete description of this specimen is provided herein. This study examines also the taxa of the Trechus “subnotatus” group, sensu Jeannel (1927), in the Balkans, focusing on uncertainties in the known taxonomic characters that differentiate species and subspecies. As a result, new data on the distribution of T. cardioderus cardioderus Putzeys, 1870 are obtained, reported for the first time from Croatia, Slovenia, and Bosnia and Herzegovina. In addition, T. cardioderus athonis Schatzmayr, 1909 is recorded for the first time from Montenegro and Bosnia and Herzegovina, while T. cardioderus goleshnicensis Apfelbeck, 1918 should be excluded from the fauna of Bulgaria.